The Effects of COVID-19 on Clinical Outcomes of Non-COVID-19 Patients Hospitalized for Upper Gastrointestinal Bleeding during the Pandemic - Pausawasdi N. (2023)
This study aims to investigate the effects of COVID-19 on clinical outcomes of non-COVID-19 patients hospitalized for upper gastrointestinal bleeding (UGIB) during the pandemic. A retrospective review is conducted. We recruited patients with UGIB admitted during the pandemic’s first wave (April 2020 to June 2020), and the year before the pandemic. The outcomes between the two groups were compared using propensity score matching (PSM). In total, 60 patients (pandemic group) and 460 patients (prepandemic group) are included. Patients admitted during the pandemic (mean age of 67 ± 14 years) had a mean Glasgow–Blatchford score of 10.8 ± 3.9. They were older (p = 0.045) with more underlying malignancies (p = 0.028), had less history of NSAID use (p = 0.010), had a lower platelet count (p = 0.007), and had lower serum albumin levels (p = 0.047) compared to those admitted before the pandemic. Esophagogastroduodenoscopy (EGD) was performed less frequently during the pandemic (43.3% vs. 95.4%, p < 0.001). Furthermore, the procedure was less likely to be performed within 24 h after admission (p < 0.001). After PSM, admissions during the pandemic were significantly associated with decreased chances of receiving an endoscopy (adjusted odds Ratio (OR), 0.02; 95% CI, 0.003–0.06, p < 0.001) and longer hospital stay (adjusted OR, 2.17; 95% CI, 1.13–3.20, p < 0.001). Additionally, there was a slight increase in 30-day mortality without statistical significance (adjusted OR, 1.92; 95% CI, 0.71–5.19, p = 0.199) and a marginally higher rebleeding rate (adjusted OR, 1.34; 95% CI, 0.44–4.03, p = 0.605). During the pandemic, the number of EGDs performed in non-COVID-19 patients with UGIB decreased with a subsequent prolonged hospitalization and potentially increased 30-day mortality and rebleeding rate.